(untitled) (Bangladesh Agronomy Journal, 2020)
A field experiment was conducted at Agronomy Field Laboratory, Patuakhali Science and Technology University, Dumki, Patuakhali from July 2018 to November 2018 to evaluate the effect of sunflower residues and herbicides on the yield and economic performance of transplanted Aman rice. Weed control methods tested were T1 = weedy check (Unweeded control), T2 = Weed-free check by hand weeding twice, T3 = Pendimethalin, T4 = Pretilachlor, T5 = Butachlor, T6 = Pyrazosulfuron ethyl, T7 = Bensulfuron methyl + Acetachlor, T8 = Bispyriback sodium, T9 = 2,4-D amine, T10 = MCPA, T11 = Sunflower residues, T12 = Sunflower residues + 100% Pyrazosulfuron ethyl, T13 = Sunflower residues + 75% Pyrazosulfuron ethyl, T14 = Sunflower residues + 50% Pyrazosulfuron ethyl. The experiment was laid out in a randomized complete block design with fourteen treatments replicated thrice. Weedy check registered significantly the highest total weed density (354.67 m-2) and total weed dry matter (51.81 g-2) while weed-free treatment by hand weeding twice recorded significantly the lowest total weed density (6.67 m-2) and total weed dry matter 0.49 g-2) . Weedy check produced the highest weed index (34.24%) and hand weeding produced the lowest. Among different herbicides applied alone, butachlor had the lowest total weed density (15 m-2) and total weed dry matter (6.43 g-2) after hand weeding. Hand weeding recorded the highest grain yield (5.14 t ha-1) which was statistically similar to pendimethalin, pretilachlor, butachlor, bensulfuron methyl + acetachlor and sunflower residues + 100% pyrazosulfuron ethyl. Higher grain yield was attributed to a higher number of panicle m-2, number of filled grains panicle-1 and 1000-grain weight. The highest gross margin (22955 Tk. ha-1) and benefit-cost ratio (1.32) were obtained from butachlor. Integration of sunflower residues with pyrazosulfuron ethyl produced effective weed suppression and satisfactory yield comparable to butachlor. Although the integration is less profitable than butachlor the farmers can use this technology as a feasible and environmentally sound approach in transplanted Aman rice field. Bangladesh Agron. J. 2020, 23(1): 47-58